Pengembangan Multimedia Interaktif Berbasis Problem Solving Pada Materi Organ Pernafasan Manusia Kelas V SD Ketangi Purworejo - Suyati Prihatin; Nurhidayati Nurhidayati; Nur Ngazizah (Departement of Mathematics Education, 2024)
This development aims to (1) develop interactive multimedia based on problem solving on class V respiratory organs material at Ketangi Purworejo State Elementary School (2) determine the feasibility of problem solving based interactive multimedia on class V respiratory organs material at Ketangi Purworejo State Elementary School. This research uses a 4D model (Define, Design, Develop, Disseminate) to complete this thesis. In this research, the researcher took subjects in class V of SD Negeri Ketangi Purworejo, totaling 17 students. This research produces data using observation, interviews and documentation methods. The questionnaire sheets in this research are validation sheets from media experts, material experts, practitioners, and student.The results of the research and development obtained are, (1) Producing the development of interactive multimedia based on problem solving on class V respiratory organ material at SD Negeri Ketangi Purworejo. This research uses the 4D model (Define, Design, Develop, Disminate), (2) the feasibility of the product is obtained The average percentage is 94.4% with the criteria being very feasible and practical. The product gets a percentage of 77.5% with the criteria being very practical. It can be concluded that interactive multimedia based on problem solving in class V respiratory organ material at Ketangi Purworejo State Elementary School can be used because it meets the criteria. feasible, and practical.